Job Analysis of Social Pedagogues in Secondary Schools: Opinion Survey of Social Pedagogues and Social Workers - Buzaitytė-Kašalynienė, Jolita (Acta Paedagogica Vilnensia, 2003)
Social pedagogue is new but rapidly developing profession in Lithuanian secondary schools. This article presents results of the social pedagogues' and social workers' job analysis research in Lithuanian secondary schools. It reveals content and peculiarities of social pedagogues’ tasks and activities. Data analysis reveals that social pedagogues’ job conditions are not good enough because only half of them have separate room, they don't have materials for activities with students and there is no funds for home visits' travel expenses. They mostly work with students of age from 9 to 14 and the problems they mostly have to deal with are school attendance, inappropriate students' behaviour, material problems, parents’ alcohol abuse and child neglect. Data analysis also reveals that most frequently performed job aims l tasks working with students, student’s groups, parents and school administration coincide with most important. Evaluation of students’ needs mostly relies on family material and living conditions hut not on family relations or child development history. Information about students mostly are gathered from teachers but not from interviews with students or direct observations. Although social pedagogues feel supported by school administration they have some disagreements. Social pedagogues don't agree with a demand to organize student’s free lunches. Social pedagogues feel that during their studies they didn’t get enough skills in counselling, group work and knowledge in psychology and law. They think that their work can be improved by better work conditions: separate room, telephone, activity appliances and money for home visits, by higher salaries and fewer social pedagogues in schools or better developed network of social services and out-of-school activity centres. This research material could help to make some changes in Social pedagogues’ job instructions: to make their tasks, functions and responsibilities more specific and relevant to the practice.
Keywords: Secondary School; Social Worker; Social Pedagogues; social pedagogues’ job